Improvement of Fasting Glucose in Response to Resistance Training with Emphasis on the Expression of Hepatic PGC1α and HNF4α Genes in Type 2 Diabetic Rats - Sayed Sadegh Salehi; Mojtaba Eizadi; Saeid Sedaghaty; Yaser Kazemzadeh; Sanaz Mirzayan Shanjani (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Genetic studies have supported the importance of hepatic glucose release in hyperglycemia among individuals with type 2 diabetes. This study investigated the effect of 6 weeks of resistance training on hepatocytes genes PGC1α and HNF4α expression as well as fasting glucose levels in rats with type 2 diabetes (T2D). Methods: This experimental study involved 21 male Wistar rats made obese by a 6-week high-fat diet. Subsequently, T2D was induced in 14 rats through STZ administration via intraperitoneal injection. Finally, the observed rats were divided into 3 groups (n=7): 1) non-diabetes, 2) diabetic control, 3) resistant to diabetic. The rats in the resistance group were completed resistance training for six weeks (5 times a week) by climbing a ladder while applying resistance. The control obese and control T2D groups did not participate in the resistance training. Forty-eight hours following the prolonged exercise session, hepatocytes genes PGC1α and HNF4α expression, along with serum insulin, glucose, and insulin resistance, was analyzed using One-Way ANOVA and Tukey post hoc test across different groups. Results: T2D induction led to significant decrease in insulin levels and an increase in fasting glucose, alongside increased insulin resistance and hepatocytes genes PGC1α and HNF4α expression when compared to non-diabetes rats. Resistance training resulted in a significant increase in serum insulin (p = 0.043) and a decrease in fasting glucose (p = 0.001), insulin resistance (p = 0.001) and hepatocytes HNF4α expression (p = 0.001), compared to the control diabetic group. Conclusion: Six weeks of resistance training resulted in a reduction in fasting glucose, and this improvement may be linked to a decrease in HNF4α expression and insulin resistance resulting from the resistance training.